Benefit valuation for a Cost-Benefit Analysis in the context of developing nations (National Administration Journal, 2020)
Cost Benefit Analyses can be useful tools for the appraisal of infrastructure projects and policies. The literature and guidance documents on the application of the CBA methodology are extensive. Moreover, the vast majority of this literature is focused on applications in upper and upper-middle countries (developed nations). This paper adds to this literature by exploring the issues of undertaking a benefit valuation exercise, as part of a CBA, in the context of developing nations. It provides an overview of the different methodologies to value benefits and offers guidance on some of the issues that may arise when such methodologies are implemented in a developing nation. This paper also offers general guidance to ensure a benefit valuation exercise provides a helpful tool to appraise a project in the context of a developing nation.
Keywords: Public policies; infrastructure policies; developing nations